Enviro-economic analysis of a solar-assisted double-effect vapour absorption system based cold storage. Issue 1 (31st December 2022) - De, Ramen Kanti; Ganguly, A.
ABSTRACT: Environmental dilapidation caused by conventional cold storage has become a matter of universal concern. The solar-powered vapour absorption system can be a viable solution to this problem. This paper introduces a scheme of double-effect vapour absorption system operated multi-commodity cold storage. A grid-interactive solar-based power system consisting of 45 Nos. of parabolic trough collectors and 225 Nos. of solar photovoltaic modules is designed to fulfil the total demand of 200 MWh on an annual basis. An analysis of the system is performed from the environment and economic viewpoint, considering four different cases of commodity storage. The total CO2 mitigation for multi-commodity cold storage (case iv) is about 421 tons. The study also reveals that the designed system can save a maximum carbon tax of $ 6100 for the case (iv) annually. The payback period of the system for case (iv) is estimated to be about 3.5 years.